Diaphragm‐Regulated Growth of Nanosheet Arrays of α‐Phase Ni–Co Layered Double Hydroxides on Arbitrary Substrates for Wettability Control and Rechargeable Alkaline Batteries. Issue 7 (18th April 2017) - Meng, Xinghua; Deng, Da
Abstract: Room‐temperature synthesis of α‐phase bimetallic nickel–cobalt layered double hydroxides (Ni–Co LDHs) nanosheets in the forms of arrays grown on arbitrary substrates is still a challenging task. We demonstrate a facile diaphragm‐assisted approach to grow α‐phase Ni–Co LDHs nanosheet arrays on various substrates at room temperature. The as‐synthesized nanosheet arrays can induce high surface roughness at the microscale, achieving both superoleophobicity underwater and superhydrophobicity in air, with contact angles measured for oil at 160° and for water at 154°, respectively. The nanosheet arrays of Ni–Co LDHs formed directly on 3D nickel foam substrates can be used as binder‐free electrodes for rechargeable batteries, achieving a specific capacity of 177 mA h g −1 when tested at 2000 mA g −1 . In contrast to literature reports, in which LDHs are often considered for pseudocapacitors, we suggest our electrodes are good for rechargeable alkaline secondary batteries or as battery electrodes in hybrid supercapacitors, based on battery behavior observed in our electrochemical tests. Other substrates, including titanium wires and carbon fiber papers, can be used as substrates. The as‐prepared α‐phase Ni–Co LDHs nanosheet arrays coated substrates and their derivatives (e.g., oxides, sulfides) can find many potential applications, including wastewater treatment, separation, electrochromic devices, catalysis and electrocatalysis, as well as energy storage. Abstract : Take it slow : Room‐temperature synthesis of α‐phase Ni–Co LDHs nanosheet arrays on various substrates was achieved by diaphragm‐regulated reactions, which could find many applications, including in alkaline batteries and surface wettability control.